Analysis of research hotspots in COVID-19 genomics based on citespace software: Bibliometric analysis - Pang, Xue meng; Peng, Zhao yun; Zheng, Xin; Shi, Jing jing; Zhou, Bao chen (Frontiers in Cellular and Infection Microbiology, 2022)
Abstract: Objective To analyze the current status, hotspots and frontier trends of genomics research on the outbreak of novel coronavirus disease (COVID-19) from 2019 to the present (March 2022). Methods Using citespace software to conduct statistical and visual analysis of data in each country, institutions, authors, journals, co-cited literature, keywords, etc. were published on the 2019-2022 Web of Science Core Collection Database (WOS) on the genomics of novel coronavirus pneumonia Results of related literature. Results A total of 9,121 English literatures were included. In 2021, the number of publications has increased significantly, and it is expected to continue to show a continuous upward trend in the future. The research hotspots of COVID-19 revolve around quarantine, biological management, angiotensin - converting enzyme-2, rna-dependent rna polymerase, etc. Research fronts and trends focus on molecular docking, messenger RNA, functional receptor, etc. Conclusion The research attention in the field of novel coronavirus pneumonia genomics has increased significantly in the past two years.